2018
DOI: 10.1002/bmc.4226
|View full text |Cite
|
Sign up to set email alerts
|

Residual level of dimethachlon in rice‐paddy field system and cooked rice determined by gas chromatography with electron capture detector

Abstract: In this study, a modified quick, easy, cheap, effective, rugged and safe method coupled with gas chromatography with electron capture detection was established to determine dimethachlon residues in paddy soil, rice husk, rice straw, brown rice and cooked rice. The limits of quantification of dimethachlon were 0.01 mg/kg for paddy soil, brown rice and cooked rice and 0.02 mg/kg for rice straw and rice husk. The mean recoveries were in the range 78.59-104.7% with relative standard deviation values of <10% for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Many studies have reported on the analytical methods, residue levels, and rates of degradation of dimethachlon residues on some crops and soils. According to studies, dimethachlon has a half-life of 2.5–7.75 days on crops and 8.2–15.71 days on soils. Dimethachlon poses an ecological risk; Zhang et al isolated and identified a novel dimethachlon-degrading strain Brevundimonas naejangsanensis J3 from the soils to accelerate its degradation. It was shown that soil microorganisms played an important role in the degradation of dimethachlon.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported on the analytical methods, residue levels, and rates of degradation of dimethachlon residues on some crops and soils. According to studies, dimethachlon has a half-life of 2.5–7.75 days on crops and 8.2–15.71 days on soils. Dimethachlon poses an ecological risk; Zhang et al isolated and identified a novel dimethachlon-degrading strain Brevundimonas naejangsanensis J3 from the soils to accelerate its degradation. It was shown that soil microorganisms played an important role in the degradation of dimethachlon.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing chemical pesticides has long been an effective method for preventing and controlling S. sclerotiorum (Liu et al 2018(Liu et al , 2021Oliveira et al 2013a, b). However, the current issues of pesticide reduction and fungicide-resistant strains of S. sclerotiorum have received considerable attention (Sun et al 2018;Besil et al 2018;Zhou et al 2014a, b). Although numerous pieces of research focus on alternative methods like agricultural practice, biological methods and breeding disease-resistant cultivars (Alvarez et al 2012;Grandini et al 2022;Zhang et al 2020), these methods are not always available and effective.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, most of the farmer prefers chemical method for insect pest management. This irrational use of chemical pesticides in the rice ecosystem increases the cost of production and has a long-term residual impact on the environment and biodiversity (Yaqub et al, 2017;Sun et al, 2018;). Rice is cultivated around the haor area in Boro season, using chemical pesticides is so dangerous for the aquatic biodiversity of haor areas.…”
Section: Introductionmentioning
confidence: 99%